Cryptocurrency: Еra and Field of Financial Innovations - Корнєєв, В.; Чеберяко, Оксана Вікторівна (Київський національний університет імені Тараса Шевченка, 2018)
Розглянуто сутність криптовалют, їх ризиків і перспектив розвитку в Україні та світі. Описано переваги й недоліки криптовалют. Висвітлено позиції зарубіжних центробанків та інших фінансових регуляторів стосовно криптовалют і ринків криптовалют. Запропоновано, що досвід Японії, Швейцарії, США та Англії у цьому питанні має бути використаний як фарватерний. Зазначено, що відповідна діяльність і фінансові послуги повинні ліцензуватися державою як вид професійної діяльності на стадіях утворення криптовалюти (майнінгу) та супроводження її обігу (трейдінг і фінансовий консалтинг).

Essence of cryptocurrencies is considered in the article, their risks and prospects of development in Ukraine and world. Advantages and disadvantages of crypto currency are described. Positions of foreign central banks and other financial regulators are lighted up in relation to cryptocurrencies and markets of cryptocurrencies. It is offered, that the experience of Japan, Switzerland, the United States and England in this question should be used as a fairway. It is marked that corresponding activity and financial services must be licensed by the state as a type of professional activity on the stages of formation of cryptocurrency (mining) and support of its circulation (trading and financial consulting).
Криптовалюти: ера і сфера фінансових інновацій
Keywords: криптовалюта; цифрові гроші; блокчейн-технології; майнінг; криптогаманець; ІСО; Bitcoin; Litecoin; Ethereum; Peercoin; cryptocurrency; digital money; blockchain technology; mining; crypto wallet; ISO; Peercoin.